Exploring and Mapping the Research Landscape on Innovation Capabilities: A Bibliometric Review - Dhafa Herlambang Wisanggeni; Yusuf Iskandar (TEPIAN, 2024)
In the contemporary global landscape dominated by technology, innovation emerges as a cornerstone for organizational prosperity and longevity. This study undertakes a comprehensive bibliometric review to explore the research terrain concerning innovation capabilities. It transcends the conventional view of innovation solely as the development of new products or services, emphasizing its broader scope, which includes the strategic management of ideas and knowledge through collaborative efforts. Employing advanced bibliometric techniques, the research meticulously identifies trends, academic contributions, and knowledge gaps in the field of innovation. Its primary objective is to offer actionable insights to stakeholders, enabling them to bolster their innovation strategies and effectively tackle challenges in the dynamic market environment. By delving into the multifaceted dimensions of innovation, the study highlights its crucial role in driving organizational competitiveness and resilience. Decision-makers are equipped with practical guidance, emphasizing the cultivation of a culture of creativity and the leveraging of external partnerships. In an era marked by uncertainty, the study underscores the necessity for organizations to embrace innovation as a strategic imperative. By seizing opportunities and navigating challenges adeptly, organizations can position themselves for sustained success in the digital age. Ultimately, this research transcends mere academic inquiry; it serves as a call to action for organizations to harness the transformative power of innovation for growth and transformation. By heeding the insights gleaned from this study, organizations can navigate the complexities of the modern business landscape and emerge as leaders in their respective fields.